Numerical Simulation of Tide and Tidal Current in Mangrove Creek - LI Yichun; LIU Shitong (Renmin Zhujiang)
Mangrove coast is one of the typical coasts in low latitude area.Mangrove is widely distributed in southern coastal cites of China,which is of great significance for tide resistance,shoal reinforcement,environmental protection and ecological security.However,mangrove hydrodynamics develops slowly in estuarine and coastal research.This paper establishes a two-dimensional hydrodynamic numerical model based on high-resolution scheme and ‘slot method’ to simulate and study the hydrodynamic characteristics of small-scale mangrove creek,and builds a simplified theoretical model based on water conservation to explore the relationship between maximum velocity and tide level.The results show that:The tidal current asymmetry in the creek is mainly affected by the incident tidal wave,and the topography in the creek cannot cause the alternation of asymmetric nature of tidal current;The mangrove is favorable for the flow structure in the creek to maintain the tidal flat and gather the materials;Mangrove has significant impact on the decrease of the longitudinal velocity on the tidal flat,but little effect on the transverse velocity;The density of natural mangrove has little effect on the velocity,and the increase of width of the deep channel promotes the flood-dominated tidal velocity;The tide level at maximum velocity is related to the depth-width ratio of the deep channel,the slope of the tidal flat and the scale of the deep channel,and affected by the flood-ebb time-asymmetry;The influence by tidal flat slope mainly comes from the change of tidal prism in the creek.The flood tide process is mainly controlled by the incident tidal wave at the entrance,while the ebb tide process is mainly affected by the volume of tidal prism in the creek.